Medicinal Plants Sector in Arunachal Pradesh - an Overview - Haridasan, K.; Sarmah, Anupam; Bhuyan, L. R.; Bisht, N. S. (Indian Forester, 2003)
The State of Arunachal Pradesh has been recognized as a rich storehouse for herbal medicine. Through ages, people of the State has been utilizing this plant resource to cure various ailments. But in the recent past large scale exploitation of selected species from wild and destruction of habitat has resulted in the depletion of this biological wealth. In the present study an attempt has been made to assess the current status of the resource, the trend of exploitation along with different initiatives taken for sustainable management of this important plant resource. The constraints and strategy of action plan for development has also been outlined in this paper.